NUMERACY OF IMPULSIVE AND REFLECTIVE 8th GRADE STUDENTS’ IN COVID-19 CONTEXT - Risky Dwi Yulanda; Tatag Yuli Eko Siswono; Janet Trineke Manoy (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
This study aims to describe the numeracy of 8th grade students with reflective cognitive style and impulsive cognitive style in solving problems in context of covid-19. The qualitave research involve 16 students of 8th grade in Kutai Kartanegara Regency, East Kalimantan Province. Selected each of one student with a reflective cognitive style and one student with an impulsif cognitive style with equal mathematical ability and same gender. Data collected by conducting tests and interviews. Data analysis techniques include data reduction, data presentation and conclusions. The results of the study show that numeracy of reflective student (MR) in solving questions in the context of covid-19 can access, use, interpret and communicate better than impulsive student (MI) can be seen from the results of the problem and answering interview. Reflective student very well in all aspect numeracy: access, use, interpret amd communicate.  Impulsive student is only well in the aspect of access, less in use, interpret and communicate.